Oncogenic features of PHF8 histone demethylase in esophageal squamous cell carcinoma. - Xiujing Sun; Jihui Julia Qiu; Shengtao Zhu; Bangwei Cao; Lin Sun; Sen Li; Peng Li; Shutian Zhang; Shuo Dong (PLoS ONE, 2013)
Esophageal cancer is the sixth leading cause of cancer-related deaths worldwide. It has been reported that histone demethylases are involved in the carcinogenesis of certain types of tumors. Here, we studied the role of one of the histone lysine demethylases, plant homeodomain finger protein 8 (PHF8), in the carcinogenesis of esophageal squamous cell carcinoma (ESCC). Using short hairpin RNA via lentiviral infection, we established stable ESCC cell lines with constitutive downregulation of PHF8 expression. Knockdown of PHF8 in ESCC cells resulted in inhibition of cell proliferation and an increase of apoptosis. Moreover, there were reductions of both anchorage-dependent and -independent colony formation. In vitro migration and invasion assays showed that knockdown of PHF8 led to a reduction in the number of migratory and invasive cells. Furthermore, downregulation of PHF8 attenuated the tumorigenicity of ESCC cells in vivo. Taken together, our study revealed the oncogenic features of PHF8 in ESCC, suggesting that PHF8 may be a potential diagnostic marker and therapeutic target for ESCC.